2022
DOI: 10.3389/fonc.2022.772076
|View full text |Cite
|
Sign up to set email alerts
|

Acute Phase Proteins as Early Predictors for Immunotherapy Response in Advanced NSCLC: An Explorative Study

Abstract: In the last decade, targeting the immune system became a promising therapy in advanced lung cancer stages. However, in a clinical follow-up, patient responses to immune checkpoint inhibitors widely differ. Peripheral blood is a minimally invasive source of potential biomarkers to explain these differences. We blindly analyzed serum samples from 139 patients with non-small cell lung cancer prior to anti-PD-1 or anti-PD-L1 therapies to assess whether baseline levels of albumin (ALB), alpha-1 acid glycoprotein (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…A recent pan-cancer study with 1,714 patients has shown that hypoalbuminemia predicts poor survival upon ICI treatment, but this work lacked a melanoma-speci c analysis placing these associations into the context of other melanoma-speci c biomarkers (14). Multiple studies on NSCLC showed that hypoalbuminemia was associated with poor survival after immunotherapy, which held in a multivariate analysis adjusting for treatment line, prior radiotherapy, NLR, and ECOG PS (39,40). Another study comparing several laboratory and clinical factors in metastatic melanoma reported that albumin was an independent predictor for immunotherapy response after adjustment for LDH, CRP, NLR, brain metastasis, sex, and age (41,42).…”
Section: Discussionmentioning
confidence: 98%
“…A recent pan-cancer study with 1,714 patients has shown that hypoalbuminemia predicts poor survival upon ICI treatment, but this work lacked a melanoma-speci c analysis placing these associations into the context of other melanoma-speci c biomarkers (14). Multiple studies on NSCLC showed that hypoalbuminemia was associated with poor survival after immunotherapy, which held in a multivariate analysis adjusting for treatment line, prior radiotherapy, NLR, and ECOG PS (39,40). Another study comparing several laboratory and clinical factors in metastatic melanoma reported that albumin was an independent predictor for immunotherapy response after adjustment for LDH, CRP, NLR, brain metastasis, sex, and age (41,42).…”
Section: Discussionmentioning
confidence: 98%
“…SAA proteins increase expression up to 1000-fold during the acute phase response, which is part of an attempt to restore homeostasis after an immune response or tissue insult [44]. SAA is prognostic of outcomes in NSCLC and other cancers [29,30,32], as well as efficacy and outcomes of ICI therapy [45,46]. One important point to note is that it is not yet determined how the different SAA proteins and their proteoforms individually have roles in prognosis or prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The 3.5 gr/dL was the most frequently used albumin cut-off in the included studies (n = 20) [25, 31-33, 37, 38, 40-43, 45-52, 54, 56-64], while eight studies evaluated the effect of albumin levels on survival by using albumin as a continuous measure [34,39,44,53,55,[65][66][67]. All but two studies reported HR for OS [25,36,49], while data for PFS was available in the 15 studies [25, 32, 33, 36, 40-42, 48-50, 52, 53, 57, 60, 63, 66]. Most studies tested the prognosis in patients treated with ICI monotherapy and nivolumab was the most commonly used ICI in the studies (n = 21) (Table -…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The sample sizes were variable and spanned from 44 [39] to 1714 [33]. More than half of the studies were reported from Far East (n = 15) [32, 39-52], followed by Europe (n = 12) [25,31,37,38,[53][54][55][56][57][58][59][60]]. The 3.5 gr/dL was the most frequently used albumin cut-off in the included studies (n = 20) [25, 31-33, 37, 38, 40-43, 45-52, 54, 56-64], while eight studies evaluated the effect of albumin levels on survival by using albumin as a continuous measure [34,39,44,53,55,[65][66][67].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation